Modernization in a Malay peasant society - Abdullah Taib (Universiti Kebangsaan Malaysia, 1974)
This is a preliminary study of a modernization process in a Malay peasant society in Kelantan. The aim of this paper is to show that Malay peasant who are strong adherents of Islam, are supporters of economic and political modernization, as long as such processes do not work against the principle teachings of Islam and as long they do not touch their religious values. As for as economic modernization is concerned it was shown that Malay peasants have not rejected it in any way. Either in the introduction of irrigation scheme, padi double-cropping or in the planting of tobacco the peasants are actively involved. In the field of politics, the peasants are involved directly with political parties which have shown interest in Malay problems such as having a Malay government.